Implementasi Tugas Dan Fungsi Komisi Pemberantasan Korupsi Sebagai Independent Agencies Dalam Sistem Ketatanegaraan Di Indonesia - Virna Dewi; Sri Yuliana (Universitas Sang Bumi Ruwa Jurai, 2023)
The 1945 Constitution of the Republic of Indonesia (1945 Constitution of the Republic of Indonesia) confirms that Indonesia is a constitutional state. Therefore, the administration of the state in Indonesia must uphold the values of Pancasila and the 1945 Constitution of the Republic of Indonesia, and guarantee that all citizens, together with their position before law and government, in carrying out constitutional affairs. From the perspective of this rule of law, it is the law that holds the highest command in the administration of the state. Thus, in fact the leader in administering the state is the law itself, in which there is an understanding of the recognition of the principle of legal and constitutional supremacy, adherence to the principle of limitation and separation of powers according to the constitutional system regulated in the Constitution. There are three classical functions of power in legal and political theory, namely the legislative, executive and judicial functions or called the trias politica. Problems Based on the background of the problems described above, the problems that are examined and discussed are as follows how the implementation of the duties and functions of the Corruption Eradication Commission as independent agencies in the Indonesian constitutional system and what are the obstacles to implementing the duties and functions of the Corruption Eradication Commission as independent agencies. Type of Research This research is normative juridical research or also called doctrinal research. In this type of research, law is conceptualized as what is written in laws and regulations (law in book) or law is conceptualized as rules or norms which are standards for human behavior that are considered appropriate.